2019
DOI: 10.1111/jgs.16083
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Postoperative Delirium

Abstract: BACKGROUND/OBJECTIVE Regular physical activity (PA) has been associated with improved cognitive function, but its effect on postoperative delirium (POD) has not been established. Our objectives were to determine the effect of baseline PA on the incidence of POD in older patients undergoing elective orthopedic surgery and to determine whether these effects were independent of cognitive reserve. We hypothesize that PA protects against POD by bolstering physiologic reserve needed to withstand the stressors of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…In our study we observed a significant association between pre-admission self-reported physical performance and independence status, cognitive performance and mobilization. A recent cohort study revealed that physical activity was associated with reduced risk of post-operative delirium [ 7 ] and this association was stronger and more evident among female gender. We observed a significant association between pre-admission physical activity and post-discharge reduction of cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we observed a significant association between pre-admission self-reported physical performance and independence status, cognitive performance and mobilization. A recent cohort study revealed that physical activity was associated with reduced risk of post-operative delirium [ 7 ] and this association was stronger and more evident among female gender. We observed a significant association between pre-admission physical activity and post-discharge reduction of cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of comorbidities and frailty expose elderly patients to an inter-individual variability that should be considered and managed [ 4 , 5 , 6 ]. Moreover, it has been demonstrated how admission to surgical units is responsible for lower physical and mental activity at 30 days after hospitalization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…36 Alternatively, exercise may upregulate production of brain-derived neurotrophic factor, which is involved in neurogenesis and neuroprotection. 37 Other evidence suggests that patients with impaired mobility often have white matter lesions, 38 which in turn may predispose them to delirium in the face of surgical stressors. SPPB improves delirium prediction in cardiac surgery patients; however, these were done in cohorts that are generally lower risk, compared to the frailer TAVR cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have reported that when controlled for confounding factors such as age, comorbidities, and baseline cognitive function, nutrition remains an independent risk factor for POD [ 52 , 53 ]. Similarly, preoperative physical activity level was also found to be strongly associated with POD risk [ 54 ]. Janssen et al [ 55 •] conducted a before-and-after study in elderly patients undergoing elective abdominal surgery for colorectal carcinoma or abdominal aortic aneurysm.…”
Section: Preoperative Strategies To Prevent Deliriummentioning
confidence: 99%